Infiltration Pattern of Blood Monocytes into the Central Nervous System during Experimental Herpes Simplex Virus Encephalitis. - Rafik Menasria; Coraline Canivet; Jocelyne Piret; Guy Boivin (PLoS ONE)
The kinetics and distribution of infiltrating blood monocytes into the central nervous system and their involvement in the cerebral immune response together with resident macrophages, namely microglia, were evaluated in experimental herpes simplex virus 1 (HSV-1) encephalitis (HSE). To distinguish microglia from blood monocyte-derived macrophages, chimeras were generated by conditioning C57BL/6 recipient mice with chemotherapy regimen followed by transplantation of bone morrow-derived cells that expressed the green fluorescent protein. Mice were infected intranasally with a sub-lethal dose of HSV-1 (1.2 x 10(6) plaque forming units). Brains were harvested prior to and on days 4, 6, 8 and 10 post-infection for flow cytometry and immunohistochemistry analysis. The amounts of neutrophils (P < 0.05) and "Ly6C hi" inflammatory monocytes (P < 0.001) significantly increased in the CNS compared to non-infected controls on day 6 post-infection, which corresponded to more severe clinical signs of HSE. Levels decreased on day 8 for both leukocytes subpopulations (P < 0.05 for inflammatory monocytes compared to non-infected controls) to reach baseline levels on day 10 following infection. The percentage of "Ly6C low" patrolling monocytes significantly increased (P < 0.01) at a later time point (day 8), which correlated with the resolution phase of HSE. Histological analysis demonstrated that blood leukocytes colonized mostly the olfactory bulb and the brainstem, which corresponded to regions where HSV-1 particles were detected. Furthermore, infiltrating cells from the monocytic lineage could differentiate into activated local tissue macrophages that express the microglia marker, ionized calcium-binding adaptor molecule 1. The lack of albumin detection in the brain parenchyma of infected mice showed that the infiltration of blood leukocytes was not necessarily related to a breakdown of the blood-brain barrier but could be the result of a functional recruitment. Thus, our findings suggest that blood monocyte-derived macrophages infiltrate the central nervous system and may contribute, with resident microglia, to the innate immune response seen during experimental HSE.